Enquête nationale sur la possession et les usages des technologies parmi les enseignants du primaire - Rasolohery, Hasiniavo; Mitchell, Joel (EdTech Hub, 2025)
This document presents a report of a national survey on technology ownership and usage among primary school teachers in Madagascar, conducted in 2023. The survey, a collaboration between EdTech Hub, the National Institute of Pedagogical Training (INFP), and the Ministry of National Education, aimed to gather reliable data on ICT deployment across Madagascar's 23 regions. Data was collected through quantitative surveys and qualitative focus groups involving 1403 educators. Key findings reveal that while 97% of educators own technological tools, basic mobile phones are most prevalent. Smartphone ownership is significant, but usage is largely limited to calls and SMS, indicating underutilisation of advanced features. Internet access is limited, with only 25.2% of teachers accessing it via smartphone. Electricity access is relatively high at 89%, primarily through the national grid and solar energy. The report highlights the need for ICT training to enhance teachers' digital skills and recommends deploying offline systems to overcome connectivity issues. It also emphasises adapting content for teachers with disabilities and considering the predominantly regional language usage in professional settings. Keywords: national teacher survey; technology access; technology use; Madagascar; primary school Ce document présente un rapport sur une enquête nationale menée en 2023 sur la possession et l’usage des technologies par les enseignants du primaire à Madagascar. Cette enquête, réalisée en collaboration entre EdTech Hub, l’Institut National de Formation Pédagogique (INFP) et le Ministère de l’Éducation Nationale, visait à recueillir des données fiables sur le déploiement des TIC dans les 23 régions du pays. Les données ont été collectées à travers des enquêtes quantitatives et des groupes de discussion qualitatifs impliquant 1 403 enseignants. Les résultats clés révèlent que, bien que 97 % des enseignants possèdent des outils technologiques, les téléphones mobiles basiques sont les plus répandus. La possession de smartphones est significative, mais leur utilisation se limite principalement aux appels et aux SMS, ce qui indique une sous-utilisation des fonctionnalités avancées. L’accès à Internet reste limité, avec seulement 25,2 % des enseignants l’utilisant via un smartphone. L’accès à l’électricité est relativement élevé (89 %), principalement via le réseau national et l’énergie solaire. Le rapport souligne la nécessité d’une formation aux TIC pour améliorer les compétences numériques des enseignants et recommande le déploiement de systèmes hors ligne pour pallier les problèmes de connectivité. Il met également l’accent sur l’adaptation des contenus aux enseignants en situation de handicap et sur la prise en compte de l’usage majoritaire des langues régionales dans les environnements professionnels. Mots clés: enquête nationale des enseignants; accès à technologie; utilisation de technologie; Madagascar; Moodle; école primaire An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14995637 ZenodoArchiveConcept: 14995636 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7997034 10.5281/zenodo.7997057 10.5281/zenodo.8401936 10.53832/edtechhub.1100 2405685:4MWP8553 2405685:5DJ69UTD
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Radio: A Rapid Evidence Review - Damani, Kalifa; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of radio in education in low- and middle-income countries (LMICs). The present RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread shutdown of schools. It, therefore, highlights transferable insights that may be applicable to educational responses resulting from the limitations caused by COVID-19. Established approaches to delivering distance education have renewed salience during this period because many students cannot access schooling in a school building due to social distancing requirements. As one of the longest-serving and most accessible types of educational technology (EdTech), and one that has had some success in education delivery in an LMIC context that was affected by an epidemic, it is particularly useful to focus on radio (Barnett et al., 2018; Hallgarten, 2020). Notably, the RER aims neither to advocate nor discourage the use of radio in education in response to the COVID-19 pandemic. Instead, it provides an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential of radio in education delivery.
ZenodoArchiveID: 4556932 PreviousDOI: 10.5281/zenodo.4477141 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3948149 10.5281/ZENODO.4556932 10.5281/zenodo.4477141 10.5281/zenodo.4556932 2259720:DSXFK6JB 2339240:4JRWSL6I 2339240:8YVF7D5N 2339240:EPCMUN8C 2339240:FKFII8IK 2339240:H8YNQIY9 2339240:IJJ6TY76 2339240:QBDJ6U43 2339240:YIAFCN9T 2405685:5GBRDVHP 2405685:65UPSCK3 2405685:67BFM4C5 2405685:6CG6479A 2405685:DM6JSS9K 2405685:P8NUYK3M 2405685:PZHGV2XR 2405685:QBYZW7N2 2405685:RBUXXHAD 2405685:VHGNZV9N 2405685:X8BFH2K5 2405685:YMWE6FR6
Keywords: L:English UXZJW5DR; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:F:Educational data QWBAFGFR; TAG:F:Online and distance teaching and learning A32ARSFK; TAG:H:Audio and Radio QIAXGMEU; TAG:P:Teachers DAJFZBM8; TAG:W:Low connectivity and/or electricity KET3PKDI; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:F:Educational data QWBAFGFR; _T:F:Online and distance teaching and learning A32ARSFK; _T:H:Audio and Radio QIAXGMEU; _T:P:Teachers DAJFZBM8; _T:W:Low connectivity and/or electricity KET3PKDI; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Messaging Apps, SMS, and Social Media: A Rapid Evidence Review - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing research on the use of mobile phone-based messaging (including SMS, and messaging through apps such as WhatsApp) to support education in low- and middle-income countries (LMICs). This topic was chosen as the focus for a RER in response to the Covid-19 pandemic and school closures, as this form of technology has been adopted as part of some countries’ methods of providing continuing education during closures and disruption. As such, the overall purpose of this document is to summarise the existing research literature around messaging, so that the existing evidence can be used to inform ongoing responses to the pandemic. The findings are intended to be of use to educational decision makers, including donors and those in government and NGOs, to inform responses to the current pandemic.
ZenodoArchiveID: 4556938 PreviousDOI: 10.5281/zenodo.4058181 PreviousDOI: 10.5281/zenodo.4477015 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4058181 10.5281/ZENODO.4556938 10.5281/zenodo.4477015 10.5281/zenodo.4556938 2339240:8QFLYEYK 2339240:ATYZFQ8R 2339240:CUBEJEWS 2339240:LCAUL9ZC 2339240:NISQD6JT 2339240:T2Z992XW 2339240:XMQV9Y56 2339240:YGQCMSDP 2405685:2GE8ESCR 2405685:4G8DT7ZB 2405685:4JM6QWPH 2405685:5NMCR3LL 2405685:EQVI8NMV 2405685:IU849P3E 2405685:MMTHETFR 2405685:PY3CXCH9 2405685:QSD5LYSF 2405685:XHBPFYVC 2405685:Z7P9NRWJ
Keywords: Covid-19; LMICs; SMS; Social media; TPD; WhatsApp; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; educational technology; mobile learning; refugee education; teacher professional development; text message; ⛔ No DOI found

EdTech evidence for Covid-19 response: Rapid evidence reviews of EdTech use in low-income and crisis contexts - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5512134 2405685:8M6GXINE 2405685:JGTWVQI4
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

How Can EMIS be Designed and Implemented in Ways That Make Them Used and Useful? - Adam, Taskeen; Mitchell, Joel (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at education management information systems (EMIS). EMIS are pivotal in educational administration, facilitating the digitisation of processes and data to enable informed decision-making. However, persistent challenges impede their effectiveness. We examine why it is vital to consider how EMIS are designed and implemented, particularly with regard to the needs and contexts of low- and middle-income countries (LMICs). We consider constraints in technical capacity, limited funding, and insufficient user engagement. We identify concrete, evidence-based recommendations for how to make EMIS useful and used more frequently based on current and recent research. To enhance EMIS efficacy, there is a need to underscore utility and usability, ensuring the collection of pertinent data and user-friendly interfaces. Furthermore, the social implications of EMIS data on individuals and communities must be considered in order to meet their needs. We also explore areas for further consideration and include lists of resources relevant to EMIS and questions and solutions to consider. Keywords: education management information systems (EMIS); low- and middle-income countries (LMICs); user-centred design; evidence-based decision-making; EdTech; educational administration. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10694602 ZenodoArchiveConcept: 10694601 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.10080734 10.53832/edtechhub.1015
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Cost-Effective EdTech Paper 1: A position piece on how the sector can make progress - Mitchell, Joel; D'Rozario, Jonny (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7003826 ZenodoArchiveConcept: 7003825 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7003826 10.53832/edtechhub.0118 2339240:3XB6YUXL 2405685:GXLAGDUM 2405685:RPR47JXT 2405685:ZXBB58KS
Keywords: _r:AddedByZotZen

Cost-Effective EdTech Paper 2: Good practice - Mitchell, Joel; D'Rozario, Jonny (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7106003 ZenodoArchiveConcept: 7106002 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7106003 10.53832/edtechhub.0119 2405685:Y3SBIPF9 2405685:ZVX4DTXQ
Keywords: _r:AddedByZotZen

Note de conseils sur la plateforme numérique - Messa, Angele; Koomar, Saalim; Mitchell, Joel (EdTech Hub, 2025)
This document is a guidance note on digital platforms, specifically focusing on e-learning and the use of Opale and Moodle software. It aims to support the implementation of a digital learning platform in Madagascar. The report addresses questions and challenges faced by the Ministry of National Education in developing and deploying digital educational content. It covers various aspects of e-learning, including evaluation methods, content structuring, accessibility, interactivity, and technical requirements. Key topics include different evaluation models, types of e-learning evaluation (formative and summative), guidelines for using Opale, tablet specifications for online learning, ensuring course accessibility, and using Moodle both online and offline. The document also provides a checklist for ensuring quality in e-learning course development and implementation. Keywords: e-learning; Moodle; Opale; digital platform; accessibility; usability; Madagascar Ce document est une note d’orientation sur les plateformes numériques, avec un accent particulier sur l’e-learning et l’utilisation des logiciels Opale et Moodle. Il vise à soutenir la mise en place d’une plateforme d’apprentissage numérique à Madagascar. Le rapport aborde les questions et défis rencontrés par le Ministère de l’Éducation Nationale dans le développement et le déploiement de contenus éducatifs numériques. Il traite de divers aspects de l’e-learning, notamment les méthodes d’évaluation, la structuration des contenus, l’accessibilité, l’interactivité et les exigences techniques. Les principaux sujets incluent les différents modèles d’évaluation, les types d’évaluation en e-learning (formative et sommative), les recommandations pour l’utilisation d’Opale, les spécifications des tablettes pour l’apprentissage en ligne, l’accessibilité des cours et l’utilisation de Moodle en mode en ligne et hors ligne. Le document propose également une liste de contrôle pour garantir la qualité du développement et de la mise en œuvre des cours en e-learning. Mots clés: e-learning; Moodle; Opale; platforme numériques; accessibilité; usabilité; Madagascar An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14995952 ZenodoArchiveConcept: 14995951 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7303773 10.53832/edtechhub.1101 2405685:RMJK6G6Q
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Refugee Education: A Rapid Evidence Review - Ashlee, Amy; Clericetti, Giulia; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for education of refugees in low- and middle-income countries (LMICs). The RER has been produced in response to the widespread global shutdown of schools resulting from the outbreak of Covid-19. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations caused by Covid-19. In the current global context, lessons learnt from the use of EdTech in refugee contexts — in which education is often significantly disrupted and education systems and responses are required to rapidly adapt — are salient.
ZenodoArchiveID: 4557019 PreviousDOI: 10.5281/zenodo.4477154 PreviousShortDOI: 10/ghgnf2 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3901521 10.5281/zenodo.4557019 10/ghgnf2 2339240:3KCTC7UA 2339240:5B7T9LEG 2339240:K45TP2GI 2339240:NNZ9DD54 2339240:SIV6ZELZ 2339240:W3ALIEA9 2405685:397HVPFN 2405685:4M9GTG8I 2405685:5AWZGNCG 2405685:6EUNRYPS 2405685:E56IKGK2 2405685:E6DMTNLL 2405685:TXGBLY4U 2405685:UUNEJ7FS 2405685:W9JLL7JV
Keywords: L:Refugees and migrants; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v3; _zenodo:submitted; _zenodoETH

Low-cost educational messaging in West Africa: evidence on cost-effectiveness - Mitchell, Joel; Mukankusi, Aimée; D'Rozario, Jonny (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12519241 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1033 ZenodoArchiveConcept: 12519240
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Girls’ Education and EdTech: A Rapid Evidence Review - Webb, Daniel; Barringer, Katie; Torrance, Rebecca; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of technology in supporting girls’ education in low and middle-income countries (LMICs). The RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread global shutdown of schools. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations to the continuation of schooling caused by COVID-19. Established approaches to maintaining continuity of education for the most marginalised have particular salience during this period because of the significant increase in the number of students at risk of disruption. Research consistently shows that while education across the board is negatively affected by crisis situations, the schooling of girls is disproportionately impacted. The RER aims neither to advocate nor discourage the use of technology in girls’ education in response to the present COVID-19 pandemic, but rather to provide an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential role of technology in delivering education for girls.
ZenodoArchiveID: 4737460 previousDOI: 10.5281/zenodo.4556939 PreviousDOI: 10.5281/zenodo.3958002 PreviousDOI: 10.5281/zenodo.4477168 PreviousShortDOI: 10/ghgnfc Publisher: Zenodo Version Number: 1 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3958002 10.5281/zenodo.3958002 10.5281/zenodo.4477168 10.5281/zenodo.4556939 10.5281/zenodo.4737460 2259720:36F6CWBU 2339240:23GW5XQ8 2339240:6YJ555Q6 2339240:9CAC5BI5 2339240:ABKFKG4Q 2339240:FC5RCEYW 2339240:GCYWZ39Q 2339240:GZYWFIHI 2339240:JMFNCMP8 2339240:L326GM9E 2339240:MQ8QSK5B 2339240:PB295ID7 2339240:Q8QJYXRQ 2339240:TIVTGHAA 2339240:TYYDMDPR 2339240:VFBZXUEM 2339240:VFBZXUEM; 2339240:WVUDHTHF 2405685:4XTHDWDA 2405685:6PE7ANUL 2405685:78VECZYK 2405685:ALEXQL2P 2405685:BLT5KKXG 2405685:C4JLZV3D 2405685:CZBRW85R 2405685:E4TFYPYP 2405685:IV7MEXRW 2405685:NMXFFTIB 2405685:PKS7U5LC 2405685:RTIHY6H8 2405685:S5PCWMRP 2405685:SA26Q7UG 2405685:V7VESTKX 2405685:WR37F768 2405685:YHERHZKV 2405685:YNMUHK9S 2534378:5794CXFP 2534378:5GTJL9K7 4804264:EZB37W4S
Keywords: L:English UXZJW5DR; L:Gender and education; LP: English; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted; ⛔ No DOI found; ⛔ No INSPIRE recid found

Summary: EdTech for Girls’ Education - A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Hinks, Jessica; D'Rozario, Jonny; Thinley, Sangay (EdTech Hub, 2024)
This document is a summary of a Rapid Evidence Review on EdTech for Girls' Education produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12819000 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1042 ZenodoArchiveConcept: 12818999
Keywords: _r:AddedByMyEducationEvidence

Country-Level Research Review: EdTech in Ghana - Tsapali, Maria; Major, Louis; Damani, Kalifa; Mitchell, Joel; Taddese, Abeba (EdTech Hub, 2021)
ZenodoArchiveID: 4613150 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4613150 2339240:7RV99GRF 2339240:KNG7CIPW 2405685:BHZPG5ZX 2405685:HH8PFJJE 2405685:IG4J94RS 2405685:YMAME8E6
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Country-Level Research Review: EdTech in Kenya - Myers, Christina; Kaye, Tom; Bapna, Akanksha; Williams, Ayesha; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5256847 2405685:FQP8MJIY 2405685:SNBW6BK6
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

EdTech for Girls' Education: A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; D'Rozario, Jonny; Thinley, Sangay; Mazari, Haani; Hinks, Jessica (EdTech Hub, 2025)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for girls in Southeast Asia. The review summarises how EdTech is currently being used with girls in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech for girls' education. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for girls, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for girls. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10987856 ZenodoArchiveConcept: 10987855 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1022 10.53832/edtechhub.1086 2405685:S4V6PXXU

A scoping review of technology in education in LMICs - descriptive statistics and sample search results - Haßler, Björn; McIntyre, Nora; Mitchell, Joel; Martin, Kevin; Nourie, Kristi; Damani, Kalifa; Kristi Nourie; Kalifa Damani (EdTech Hub, 2020)
EdTechHub.Copy: 2129771:GYTVIZJV EdTechHub.Copy: 2129771:MBZLFNDM EdTechHub.ThisIsNot: 2339240:2387P995 2339240:8RA9UD7W shortDOI: 10/ghgk6h KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3631588 10/ghgk6h 2129771:56GZ7UBP 2129771:9VXUZISD 2129771:ADGISTZU 2129771:GYTVIZJV 2129771:MBZLFNDM 2339240:2387P995 2339240:65KP6SVQ 2339240:6FUA4SDV 2339240:85SBE7SC 2339240:8RA9UD7W 2339240:IXIRDBKK 2339240:STPRNPV3 2405685:BBQI3VSA 2405685:CMRISZHV 2405685:F6UAIKKN 2405685:QJTH2UXC 2405685:R88UVQZ7 503888:7EH7BANW 503888:PI9FLM7C
Keywords: LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:v; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Research publication strategy and proposed publications - Haßler, Björn; McIntyre, Nora; Hollow, David; Jordan, Katy; Hennessy, Sara; Brugha, Meaghan; Mitchell, Joel (EdTech Hub, 2019)
EdTechHub.Copy: 2129771:SNH4JG9L EdTechHub.Source: 2339240:94ZP3EK4 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3624978 2129771:SNH4JG9L 2339240:94ZP3EK4 2339240:VMNDUZSF 2405685:2GLWRD86
Keywords: LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Why COVID-19 is an EdTech opportunity for Latin America - Mitchell (World Economic Forum, 2020)
The region's digital divide is hindering efforts to deliver remote learning during the pandemic. Here's how governments and start-ups can make a difference.
KerkoCite.ItemAlsoKnownAs: 2339240:TXI22394 2405685:F3H5ND3U

Systemic Mixed-Methods Research — A conceptual framework for EdTech research along the IDIA scale - Haßler, Björn; Hennessy, Sara; Hollow, David; Simpson, Lea; Carter, Alice; Damani, Kalifa; Francis, Gill; Jordan, Katy; McIntyre, Nora; Mitchell, Joel (EdTech Hub, 2019)
EdTechHub.Copy: 2129771:SLHSYDRF PreviousDOI: 10.5281/zenodo.3377829 PreviousShortDOI: 10/ghgngc KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3377828 10.5281/zenodo.3377829 10.5281/zenodo.3595482 10/ghgngc 2129771:84AIHEAJ 2129771:Q74CFTXR 2129771:SLHSYDRF 2339240:2DHE9CQC 2339240:BF96YT5K 2339240:FJZA9NPX 2339240:NLMLQD75 2405685:6YT2AIMC 2405685:7S8Z2IUF 2405685:RUSE8WYV
Keywords: LP: English; R:Mixed methods; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _dont_post_PDF; _yl:f; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

EdTech for Out-of-School Children and Youth: A Rapid Evidence Review for the Southeast Asian Region - Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D'Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for out-of-school children and youth (OOSCY) in Southeast Asia. The review summarises how EdTech is currently being used with OOSCY learners in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech with different out-of-school learners. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for OOSCY, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for OOSCY. Key words: out-of-school children; rapid evidence review; RER; Southeast Asia; ASEAN; education technology; marginalised learners An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10610797 ZenodoArchiveConcept: 10610796 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1007 2339240:SZE9FBW4 2405685:IIAMD77T
Keywords: _r:AddedByMyEducationEvidence

EdTech for Learners With Hearing and Visual Impairments: A Rapid Evidence Review for the Southeast Asian Region - Zhao, Annette; Hinks, Jessica; Thang, Sarah; Mitchell, Joel; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D'Rozario, Jonny (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with hearing and visual impairments. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education forlearners with hearing and visual impairments, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; visual impairments; hearing impairments; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11197419 ZenodoArchiveConcept: 11197418 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1027 10.53832/edtechhub.1028 2405685:DQ9GNC3J 2405685:M6A4ZHJ3
Keywords: _r:AddedByMyEducationEvidence

Summary: EdTech for Learners With Hearing and Visual Impairments - A Rapid Evidence Review for the Southeast Asian Region - Zhao, Annette; Hinks, Jessica; Thang, Sarah; Mitchell, Joel; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny (EdTech Hub, 2024)
This document is a summary of a rapid evidence review on EdTech for Learners With Hearing and Visual Impairments produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/.An output of the EdTech Hub, https://edtechhub.org/ An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12819042 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1043 ZenodoArchiveConcept: 12819041
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Summary: EdTech for Out-of-School Children and Youth - A Rapid Evidence Review for the Southeast Asian Region - Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D’Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
This document is a summary of a rapid evidence review on EdTech for Out-of-School Children and Youth produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/.An output of the EdTech Hub, https://edtechhub.org/ An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12819080 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1044 ZenodoArchiveConcept: 12819079
Keywords: _r:AddedByMyEducationEvidence

Literature search protocol for the African Education Research Database - Mitchell; Rose (Zenodo, 2018)
This methodological note provides an overview of the ‘Mapping education research in sub-Saharan Africa’ project. It presents the protocols for the literature search, data extraction, and development of the African Education Research Database.
shortDOI: 10/ghgnfp KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1245521 10/ghgnfp 2339240:3WYP59B9 2405685:CK2VGGRV
Keywords: Reviewed; _not_EdTechHub; _zenodoOTHER; education research; sub-Saharan Africa

Summary: Out-of-School Children and Youth - A Rapid Evidence Review for the Southeast Asian Region - Afzal, Nimra; Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D’Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12819080 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1044 ZenodoArchiveConcept: 12819079
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Summary: EdTech for Learners With Cognitive and Learning Disabilities - A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Thang, Sarah; Zhao, Annette; Hinks, Jessica; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny; Nimra, Afzal (EdTech Hub, 2024)
This document is a summary of a rapid evidence review on EdTech for Learners With Cognitive and Learning Disabilities produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12819139 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1045 ZenodoArchiveConcept: 12819138
Keywords: _r:AddedByMyEducationEvidence

EdTech for Learners With Cognitive and Learning Disabilities: A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Thang, Sarah; Zhao, Annette; Hinks, Jessica; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny; Afzal, Nimra (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with cognitive and learning disabilities. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. We discuss the nature of EdTech for learners living with cognitive and learning disabilities, the effectiveness of these initiatives, and barriers for accessing EdTech. The RER aims neither to advocate nor discourage the use of technology to support education for learners with coginitive and learning disabilities, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; cognitive disabilities; learning disabilities; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10987889 ZenodoArchiveConcept: 10987888 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1006 10.53832/edtechhub.1023 2339240:U7UE5PIN 2405685:B422KBGQ 2405685:PGRMI8NH
Keywords: _r:AddedByMyEducationEvidence; ⛔ No INSPIRE recid found

The role of video in teacher professional development - Marsh, Brian; Mitchell, Nick (Teacher Development, 2014)
shortDOI: 10/gf7grh KerkoCite.ItemAlsoKnownAs: 10.1080/13664530.2014.938106 10/gf7grh 2339240:6U4RC34H 2339240:NUKR7Z5G 2405685:AT5BDZWD 2405685:PUT3TV3R 2405685:QX23PU84

Deconstructing EdTech frameworks based on their creators, features, and usefulness - Cherner, Todd; Mitchell, Chyrstine (Learning, Media and Technology, 2020)
Several theoretical frameworks have been released in recent years to inform how educational technology (edtech) can be used in the classroom. These frameworks range from providing a holistic view of the role edtech plays in education at a macrolevel to analyzing how edtech is used by students and teachers. With a growing number of them now available, researchers have yet to systemically collect and analyze a set of these frameworks, which can result in edtech not being used effectively by practitioners and researchers alike. In response, this study employed a content analysis methodology to analyze nine frameworks designed for using edtech. This study will report its findings regarding the creators of these frameworks, features used to draw attention to the frameworks, and which frameworks key stakeholders may find most useful. To conclude, implications for contextualizing these frameworks within the EdTech Ecosystem will be offered along with critical considerations for practitioners and researchers to use when selecting edtech frameworks for their work.
Publisher: Routledge _eprint: https://doi.org/10.1080/17439884.2020.1773852 zotzenLib.CopiedFrom: 2339240:3IXTKVWF KerkoCite.ItemAlsoKnownAs: 10.1080/17439884.2020.1773852 2339240:3IXTKVWF 2339240:N7T4DBJN 2339240:U79BIBXS 2405685:XB6U7UD3
Keywords: Critical Media Literacy; EdTech; Frameworks

Inclusion in Vietnam: An intersectionality perspective on girls with disabilities and education - Nguyen, Xuan-Thuy; Mitchell, Claudia (Childhood, 2014)
This article explores the challenges related to the inclusion of girls with disabilities in Vietnamese schools. Building on fieldwork which interrogates the institutional treatment of girls with disabilities in the Vietnamese context, we suggest that there is a need to think more critically about the inclusion and exclusion of girls with disabilities within social and educational policies. The issues that we will discuss are taken from a theoretical and methodological standpoint. First, there is a need for rethinking the intersection between disability and gender in educational policies and practices; second, we emphasize the need for understanding the implications of inclusion and exclusion in global/national/local contexts in relation to girls with disabilities; and finally, we suggest that using innovative methodological approaches is important to foster inclusion and social change.
12 citations (Crossref) [2024-04-17] KerkoCite.ItemAlsoKnownAs: 10.1177/0907568214524459 2339240:FV2K8DIV 2405685:WT6IJ8LQ
Keywords: ⛔ No INSPIRE recid found

Access to and use of technology by primary school teachers: A survey in the 23 regions of Madagascar - Rasolohery, Hasiniavo; Koomar, Saalim; Mitchell, Joel; Mitchell, Saalim Koomar and Joel, Hasiniavo Rasolohery (EdTech Hub, 2023)
The Madagascar Ministry of National Education, through the National Institute for Pedagogical Training, plans to use new technology in teacher training for early-stage reading and writing in Malagasy. This initiative is undertaken within the framework of the Madagascar Basic Education Support Project. The main objective is to train 5,000 teachers of the T2 class remotely, drawing inspiration from systems such as the Distance Education for Primary Teachers (FADEP).

Refugee Education: A Rapid Evidence Review - Ashlee, Amy; Clericetti, Giulia; Mitchell, Joel (2020)
This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for education of refugees in low- and middle-income countries (LMICs). The RER has been produced in response to the widespread global shutdown of schools resulting from the outbreak of COVID-19. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations caused by COVID-19. In the current global context, lessons learnt from the use of EdTech in refugee contexts — in which education is often significantly disrupted and education systems and responses are required to rapidly adapt — are salient.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4557019 2339240:RD5HM47R 2405685:EXMQF7W4

How equitable are South-North partnerships in education research? Evidence from sub-Saharan Africa - Asare, Samuel; Mitchell, Rafael; Rose, Pauline (Compare: A Journal of Comparative and International Education, 2020)
This article explores equity with respect to South-North partnerships in the context of education research involving scholars based in sub-Saharan Africa. Drawing on large-scale bibliometric analysis of over 1,000 publications published in English between 2010 and 2018, it finds that participation in such partnerships favours a relatively small number of countries in sub-Saharan Africa. These collaborations appear to be reproducing gender imbalances in authorship. Complemented by interviews with 31 researchers based in the region, it further identifies examples of asymmetrical relationships alongside more positive partnerships and practices. Scholars based in sub-Saharan Africa were more likely to view partnerships initiated by researchers based in the region as equitable.
Publisher: Routledge _eprint: https://doi.org/10.1080/03057925.2020.1811638 KerkoCite.ItemAlsoKnownAs: 10.1080/03057925.2020.1811638 2339240:IDPL76GX 2405685:C54NGNMP
Keywords: Education; South-North research partnerships; sub-Saharan Africa; sustainable development goals

How Accessible are Journal Articles on Education Written by Sub-Saharan Africa-based Researchers? - Asare, Samuel; Mitchell, Rafael; Rose, Pauline (Development and Change, 2021)
This article investigates the extent to which education publications authored by researchers based in sub-Saharan Africa are published as open access (OA). We draw on bibliometric analysis of 1,858 peer-reviewed articles over the period 2010‒18, together with interviews with 31 academics based in the region. Overall, we find a steady increase in OA publishing in the region over this period, although the proportion of OA publications remains low. The study finds that: (1) open access articles by researchers in sub-Saharan Africa are concentrated in journals with a lower impact factor; and (2) authors in sub-Saharan Africa tend to publish in higher quality journals behind a paywall, rather than in lower quality journals that either have no or lower cost for open access.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/dech.12639 KerkoCite.ItemAlsoKnownAs: 10.1111/dech.12639 2339240:AK4DTNUU 2405685:M7Q436YL

Access to and use of technology by primary school teachers: A survey in the 23 regions of Madagascar - Rasolohery, Hasiniavo; Koomar, Saalim; Mitchell, Joel (EdTech Hub, 2023)
The Madagascar Ministry of National Education, through the National Institute for Pedagogical Training, plans to use new technology in teacher training for early-stage reading and writing in Malagasy. This initiative is undertaken within the framework of the Madagascar Basic Education Support Project. The main objective is to train 5,000 teachers of the T2 class remotely, drawing inspiration from systems such as the Distance Education for Primary Teachers (FADEP).
KerkoCite.ItemAlsoKnownAs: 2339240:V4Z9QSPV 2405685:9NYHCGPM

No lost generation: Supporting the school participation of displaced Syrian children in Lebanon - de Hoop, Jacobus; Morey, Mitchell; Seidenfeld, David (Journal of Development Studies, 2019)
This study documents the impact of a cash transfer programme–known as the No Lost Generation Programme (NLG) and locally as Min Ila (‘from to’)–on the school participation of displaced Syrian children in Lebanon. An initiative of the government of Lebanon, the United Nations Children’s Fund (UNICEF), and the World Food Programme (WFP), the programme provided cash for the benefit of children enrolled in afternoon shifts at public primary schools. It was designed to cover the cost of commuting to school and to compensate households for income forgone because children were attending school instead of working. Commuting costs and forgone income are two critical barriers to child school participation. The analysis relies on a geographical regression discontinuity design to identify the impact halfway through the first year of programme operation, the 2016/2017 school year. The analysis finds substantive impacts on school attendance among enrolled children, which increased by 0.5 days to 0.7 days per week, an improvement of about 20 per cent relative to the control group. School enrolment among Syrian children rose rapidly across all Lebanon’s governorates during the period of the evaluation, resulting in supply-side capacity constraints that appear to have dampened positive enrolment impacts.
Publisher: Routledge KerkoCite.ItemAlsoKnownAs: 10.1080/00220388.2019.1687875 2405685:6254DV2I

Responding to the COVID-19 pandemic in Trinidad and Tobago: Challenges and opportunities for teacher education - Kalloo, Rowena Constance; Mitchell, Beular; Kamalodeen, Vimala Judy (Journal of Education for Teaching, 2020)
Trinidad and Tobago responded decisively to the COVID 19 pandemic and was successful in containing community spread of the virus. By mid-march 2020, there was closure of key business and educational institutions. To minimise the loss of learning time, emergency remote learning became the modus-operandi, a response which challenged the most socially vulnerable students. At the University of the West Indies (UWI) the 500 participants enrolled in the Early Childhood, and Primary education programmes, and the in-service post-graduate diploma in Secondary education were struggling to adjust to online teaching, the existential anxiety of coping with a dangerous disease, and programme completion. The UWI instituted a COVID-19 policy that facilitated a structured response to programme completion and assessment across all faculties.The paper analysed the decisions taken by the UWI School of Education that supported its teachers through the practicum and pedagogy courses. Using a qualitative case study methodology, data were collected through observations, documents, and informal discussions with faculty. Thematic analyses allowed the emergence of three key constructs that facilitated effective learning during the crisis period : Community as an empathetic connection to stakeholders, Creativity as the ability for agile and imaginative responses, and Connectivity through technological readiness.
Publisher: Routledge KerkoCite.ItemAlsoKnownAs: 10.1080/02607476.2020.1800407 2405685:3XSGDCJY
Keywords: COVID-19; Teacher education; inequities; online education

Mapping the landscape of education research by scholars based in sub-Saharan Africa Insights from the African Education Research Database - Rose, Pauline; Downing, Pheobe; Asare, Samuel; Mitchell, Rafael (Zenodo, 2019)
This report outlines key features of education research undertaken by scholars based in sub-Saharan Africa, as represented in the African Education Research Database. The database catalogues social science research with implications for education policy and practice in sub-Saharan Africa, published in reputable journals and written by at least one researcher based in the region. In exclusively cataloguing research conducted by researchers based in sub-Saharan Africa, the African Education Research Database is a unique resource for educational development research and policy in the region.
shortDOI: 10/ggjnpx KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3242314 10/ggjnpx 2339240:PEDMUGX2 2339240:QGS6S4IS 2405685:JA5F2U7R 2405685:ZM2IB7JE
Keywords: Reviewed; _zenodoOTHER

"Let's not leave this problem": exploring inclusive education in rural South Africa - Mitchell, Claudia; De Lange, Naydene; Thuy, Nguyen-Thi Xuan (Prospects: Quarterly Review of Comparative Education, 2008)
Inclusive education represents a new agenda for educational reform that spans a wide range of socio-political, cultural, ethical, personal and interpersonal dimensions. Working towards educational inclusion demands commitments, responsibilities and initiatives on the part of all parties to take into consideration the meanings and purpose of education and social justice, to engage and take collective actions in their struggle to combat the diverse forms of educational and social exclusion. This paper presents an educational initiative to implement inclusive education in rural KwaZulu-Natal, an area of South Africa that is most seriously affected by the pandemic of HIV and AIDS. Through the implementation of participatory video-making projects in two schools, the authors seek to empower the voices and actions of teachers in an effort to cope with the problems of poverty and marginalization facing many children. The outcomes of this type of participatory work with teachers have implications for the policy-making process, which in turn, could change the ways educational policy research is structured and implemented.
Publisher: Springer, 233 Spring Street, New York, NY 10013 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/61950460?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1007/s11125-008-9057-y 2339240:BV8QZH7J 2405685:G5SZS5H6 2405685:X66PVJWQ 2534378:RJ6ZCAD4 2534378:TTCJ2RZE 2534378:WG3HWTSN
Keywords: Access to Education; Acquired Immunodeficiency Syndrome (AIDS); Developing Nations; Disabilities; ERIC; Current Index to Journals in Education (CIJE); Education; Education reform; Educational Change; Educational Policy; Foreign Countries; Human immunodeficiency virus–HIV; Inclusive Schools; Mainstreaming; Multicultural education; Policymakers; Poverty; Researchers; Rural Areas; Rural areas; Social Attitudes; Social Bias; Social Isolation; Social Justice; Social activism; South Africa; Special Needs Students; Teacher Attitudes; __:import:01; __:match:final; __:matched; __:study_id:2098725; __finaldtb

First Lessons from Our Study: Optimising Messaging for Returns to School - Kably, Nathan; Mitchell, Joel; Zhao, Annette; D'Rozario, Jonny (EdTech Hub, 2023)
This blog examines the valuable insights gained from EdTech Hub's initial research on the use of messaging (primarily text messaging) to assist caregivers in promoting their children's school attendance. In this blog, we delve into the workings of messaging mechanisms and share our study findings. Additionally, we outline critical considerations for those interested in developing a comparable intervention. Read on to learn more...
KerkoCite.ItemAlsoKnownAs: 2339240:4T3GP6TA 2405685:IQRXCPLV

Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) - Haßler, Björn; Brugha, Meaghan; Muyoya, Chisenga; Mitchell, Joel; Hollow, David; Jackson, Alan (Jigsaw and Open Develoment & Education, 2018)
Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) Also available at https://digitalprinciples.org/resource/donor-organizations-the-principles-for-digital-development-a-landscape-assessment-and-gap-analysis/, https://digitalprinciples.org/wp-content/uploads/PDD2018_interactive.pdf
EdTechHub.Source: 2129771:I2CG3TP3 shortDOI: 10/ghgk6z KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1204703 10/ghgk6z 2129771:I2CG3TP3 2129771:SI7RBL6P 2405685:46SDL9HI
Keywords: _DOILIVE; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
ZenodoArchiveID: 7267302 ZenodoArchiveConcept: 7267301 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7267302 10.53832/edtechhub.0127 2339240:V7ARHU93 2405685:GBBGHCBH 2405685:QADQUWU3 2405685:UTTZNZ24
Keywords: _r:AddedByZotZen

Country-level research review: Sierra Leone - Kallon Kelly, Christiana; Koomar, Saalim; Kreimeia, Adam; McBurnie, Chris; Mitchell, Joel; Myers, Christina (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:746WTJF3 2405685:HNVAP5QB
Keywords: dode_eth-src-eth

Radio Instruction to Strengthen Education (RISE) in Zanzibar. Learning gains assessment: more than child's play. - Morris, Emily; Philip, Miriam; Othman, Abrahman Faki; Mitchell, James; Quiones, Esteban J.; Leatxe, Denisse (Education Development Center, Inc. and Ministry of Education and Vocational Training, 2009)
Students at a RISE learning center, who now have access to an early childhood education. RADIO INSTRUCTION TO STRENGTHEN EDUCATION (RISE) IN ZANZIBAR LEARNING GAINS ASSESSMENT:…
KerkoCite.ItemAlsoKnownAs: 2339240:B9UUQVJH 2405685:9E3KIGN5

Affordable online maths tuition: Evaluation report and executive summary. - Torgerson, Carole; Ainsworth, Hannah; Buckley, Hannah; Hampden-Thompson, Gillen; Hewitt, Catherine; Humphry, Deborah; Jefferson, Laura; Mitchell, Natasha; Torgerson, David (Education Endowment Foundation, 2016)
KerkoCite.ItemAlsoKnownAs: 2339240:BEA4Y4D2 2405685:J3GWGJX9
Keywords: ⛔ No DOI found

Teacher Professional Development in Africa: A Critical Synthesis of African Research Evidence - Mitchell, Rafael; Ayinselya, Roger A.; Barrett, Angeline M.; Cortez, Artemio; David, Opanga; Imaniriho, Dan; Nwako, Zibah; Reda, Nigusse Weldemariam; Singh, Marcina (Zenodo, 2024)
This study is an original synthesis of African research evidence on teacher professional development (TPD) provision in the sub-Saharan region. It provides a critical appraisal of the evidence base and identifies patterns in the actors and agendas involved in TPD initiatives; the modes and modalities of provision; and teachers’ experiences and outcomes. The study takes the form of a critical interpretive synthesis (CIS) and is informed by theoretical work on decolonising education (Ndlovu-Gatsheni 2013) and promoting Gender Equality and Social Inclusion (GESI). It draws primarily on publications by African-based researchers, where our research team is largely based. The findings point to the prevalence of one-size-fits-all provision can which often undermine, rather than strengthen, the situated professional knowledge and agency of teachers. Additionally, despite the emphasis given to inclusive education and gender-responsive pedagogy as a substantive focus of TPD initiatives, we find that dominant modalities of TPD provision continue to exclude historically marginalised groups, and largely reproduce existing social inequalities along the lines of gender, rurality, dis/ability and other dimensions. Alongside these negative findings, the study also finds fertile ground for more inclusive, generative and empowering TPD in the region.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.12731754 2339240:EG93FIXN 2405685:WRI9SIYF
Keywords: Educational sciences

The State of Global Learning Poverty: 2022 Update - Azevedo, Joao Pedro; Rogers, Halsey; Ahlgren, Ellinore; Akmal, Maryam; Cloutier, Marie-Helene; Ding, Elaine; Raza, Ahmed; Ning Wong, Yi; Montoya, Silvia; Chakroun, Borhene; Chang, Gwang-Chol; Guerriero, Sonia; et al. (The World Bank, 2022)
KerkoCite.ItemAlsoKnownAs: 2339240:MTNZJFPM 2405685:I5JFXK3N